2016
DOI: 10.1016/j.amjcard.2015.12.062
|View full text |Cite
|
Sign up to set email alerts
|

Carotid Plaque Characterization, Stenosis, and Intima-Media Thickness According to Age and Gender in a Large Registry Cohort

Abstract: Carotid intima-media thickness (CIMT) is a well-established predictor of cardiovascular disease events. Not well described, however, is the prevalence of plaque and stenosis severity and how this varies according to extent of CIMT, age, and gender. We evaluated the extent of carotid plaque and stenosis severity according to CIMT, age, and gender in a large CIMT screening registry. We studied 9,347 women and 12,676 men (n = 22,023) who received carotid ultrasound scans. The presence and severity of both carotid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
34
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 49 publications
(37 citation statements)
references
References 26 publications
2
34
0
1
Order By: Relevance
“…23, 24 Consistent with previous studies, this study found that older age and cigarette smoking were associated with the presence of carotid plaque, with age being the most robust predictor of subclinical atherosclerosis. 25, 26 In stratified comparisons, however, age was associated with carotid plaque only in overweight and obese participants, but not among participants of normal weight.…”
Section: Discussionmentioning
confidence: 92%
“…23, 24 Consistent with previous studies, this study found that older age and cigarette smoking were associated with the presence of carotid plaque, with age being the most robust predictor of subclinical atherosclerosis. 25, 26 In stratified comparisons, however, age was associated with carotid plaque only in overweight and obese participants, but not among participants of normal weight.…”
Section: Discussionmentioning
confidence: 92%
“…For instance, at least some buildup of CAPs is found in: a) 48% of men and 36% of women younger 45 years; b) 71% of men and 54% of women between the ages of 50–54 years; and c) 94% of men and 93% of women 80 years or older 30 . Thus, having shorter LTL might not apply to all individuals with carotid artery atherosclerosis.…”
Section: Discussionmentioning
confidence: 99%
“…Carotid artery stenosis is a serious condition that is usually caused by atherosclerosis [25]. As with coronary atherosclerosis, inflammation plays a pivotal role in carotid atherosclerosis from initiation through progression [26].…”
Section: Discussionmentioning
confidence: 99%